2006
DOI: 10.1119/1.2174031
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting elementary quantum mechanics with the BenDaniel-Duke boundary condition

Abstract: The past decade has seen an upsurge of interest in quantum dots and nanostructures. These are essentially structures of size 1to10nm. We discuss a simplified model of a quantum dot in which we employ the effective mass approximation and the BenDaniel-Duke boundary condition. The latter accounts for the fact that the effective carrier mass inside the well, mi, is different from the mass outside, m0. The energies and the charge distributions in the nanostructure are determined by the mass discontinuity factor β=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…As discussed by Reboredo and Zunger [30] however, the physical nature of the barrier can influence the symmetry of the dot levels as well, without appreciably altering the excitonic transition energy. Furthermore, Singh and Kumar [31] recently showed that the mismatch of the value of the effective masses between barrier and dot material can have large effects on the NC energy levels, as a consequence of the BenDanielDuke boundary conditions [32]. The main difference between the calculations of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed by Reboredo and Zunger [30] however, the physical nature of the barrier can influence the symmetry of the dot levels as well, without appreciably altering the excitonic transition energy. Furthermore, Singh and Kumar [31] recently showed that the mismatch of the value of the effective masses between barrier and dot material can have large effects on the NC energy levels, as a consequence of the BenDanielDuke boundary conditions [32]. The main difference between the calculations of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum dots may be an alternative to incorporation of fillers in adhesive resins. Quantum dots are inorganic particles about 1 to 10 nm, obtained via semiconductor materials (Singh and Kumar 2006). These nanocrystals, also known as "artificial atoms," are used for applications in materials for engineering (Matsuyama et al 2012;Feng et al 2015;Padovani et al 2015) and bioengineering (Khani et al 2011;Bilan et al 2015;Hosseinzadeh et al 2016) due to the fluorescence and suspension in colloidal medium attributed to quantum confinement (Matsuyama et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This heterojunction can de-modeled by a quantum well (QW), essentially a finite square well, with BenDaniel-Duke boundary conditions. Such a problem was recently discussed by several authors, like Singh et al [11,12], who replaced the trigonometric functions entering in the transcendental equations for the bound states energy by the first few terms of their series expansion; in this way, the equations become simple, tractable algebraic ones. Our approach is different, being based on a more sophisticate "algebraization" of trigonometric functions, as proposed by de Alcantara Bonfim and Griffiths [8].…”
Section: Introductionmentioning
confidence: 99%